2001
DOI: 10.2214/ajr.176.2.1760303
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Radiation Dose for Pediatric Body Applications of Single-Detector Helical CT

Abstract: Adjustments of the standard helical CT protocols for adults can result in reduced radiation dose when imaging children. It is the radiologist's responsibility to critically evaluate the CT techniques used at their institution. Adjustments to CT protocols should be made to choose the appropriate mA and pitch when imaging children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
187
0
14

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(204 citation statements)
references
References 15 publications
3
187
0
14
Order By: Relevance
“…Recent reports in the literature concerning an increased cancer risk in children undergoing CT scans recommend radiation dose reduction for children [8,9]. Approximately one half of pediatric surgeons who completed an anonymous survey recognized this increased cancer risk [10].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports in the literature concerning an increased cancer risk in children undergoing CT scans recommend radiation dose reduction for children [8,9]. Approximately one half of pediatric surgeons who completed an anonymous survey recognized this increased cancer risk [10].…”
Section: Discussionmentioning
confidence: 99%
“…This method ensures that thicker regions of the body are imaged using higher tube currents than thinner, less attenuating areas. Within each imaged section, user-specified noise indices are chosen, which predict an acceptable level of image noise, thereby preserving diagnostic quality while minimising radiation exposure [24,25]. The higher the noise index chosen by the radiologist, the greater the noise in the CT image and the lower the radiation dose required to acquire the image.…”
Section: Low-dose Ct Technologymentioning
confidence: 99%
“…Recent studies in pediatric CT have shown that it is unacceptable to use a tube current setting that is appropriate for an adult on a child (85,95,96). Reductions in tube current or gantry speed have recently been introduced that decrease the radiation dose in pediatric CT (97)(98)(99). It is a welcome sign that most major manufacturers have recently added dose-reduction features specifically geared toward pediatric patients, and initiated user education programs for CT dose control (43).…”
Section: Patient Sizementioning
confidence: 99%